Effects of Fungicide and Herbicide Chemical Exposure on Apis and Non-Apis Bees in Agricultural Landscape - Belsky, Joseph; Joshi, Neelendra K. (Frontiers in Environmental Science, 2020)
Fungicide and herbicide chemistries are commonly applied in agricultural production systems and other agricultural landscapes during flowering periods which are concurrent with the timing of bee-dependent pollination services in many plant species. As a result, bees can be exposed to these pesticides while foraging crops and other flowering plants in the landscape where they have been administered. Laboratory and semi-field studies simulating these pesticide exposure scenarios have demonstrated lethal and sub-lethal impacts to both Apis and non-Apis species of domesticated bees. Exposure to fungicides and herbicides has also been attributed to bee genetic and molecular level changes in some cases. Herbicides can also indirectly impact bees as a result of decreasing weeds and other flowering plants that serve as nutrient resources for foraging bees. We analyze a series of recent studies concerning the toxicity of fungicides and herbicides to Apis and non-Apis bees as a basis for forming our views on key priorities regarding the direction of future research initiatives in this area. Exploring impacts of agricultural pesticides beyond insecticides to bees is timely given documented bee declines in the last decade and resulting widescale interest in identifying different drivers of these declines among the biological and ecological scientific communities.